Biochemical Composition of Some Selected Aquatic Macrophytes Under Ex-Situ Conditions (Journal of the Asiatic Society of Bangladesh, Science, 2018)
Ex-situ culture studies of five selected aquatic macrophytes, namely Nymphaea nouchali Burm. f., Enhydra fluctuans Lour., Ipomoea aquatica Forsk., Hygroryza aristata (Retz.) Nees ex Wight & Arn. and Limnocharis flava (L.) Buch. were carried out. Comparing the biochemical composition of the above mentioned five aquatic macrophytes, on an average, Enhydra fluctuans was found to contain highest amounts of proteins (18.20%) and Ipomoea aquatica contains highest amounts of carbohydrate (58.60%). Lowest amounts of proteins (14.35%) were recorded in Hygroryza aristata and Limnocharis flava. On the other hand lowest amounts of carbohydrates were obtained in Nymphaea nouchali. Ipomoea aquatica contained highest amounts of energy (321.23 kcal) and lowest amount was observed in Limnocharis flava. The five aquatic plants were low in fiber, fat and also in ash. Among all the five aquatic macrophytes, highest values of calcium and phosphorus were found to be present in Limnocharis flava and iron was highest in Nymphaea nouchali. Lowest values of calcium and phosphorus were present in Ipomoea aquatica and lowest amount of iron was present in Limnochris flava. The present study demonstrated that, these five aquatic macrophytes are the important sources of carbohydrate, protein and minerals, which are suitable for incorporation in human diet and feed also.Asiat. Soc. Bangladesh, Sci. 44(1): 53-60, June 2018